Group‐in‐a‐Box Meta‐Layouts for Topological Clusters and Attribute‐Based Groups: Space‐Efficient Visualizations of Network Communities and Their Ties. (2nd June 2014) - Chaturvedi, S.; Dunne, C.; Ashktorab, Z.; Zachariah, R.; Shneiderman, B.
<x xml:space="preserve">Abstract</x> An important part of network analysis is understanding community structures like topological clusters and attribute‐based groups. Standard approaches for showing communities using color, shape, rectangular bounding boxes, convex hulls, or force‐directed layout algorithms remain valuable, however our Group‐in‐a‐Box meta‐layouts add a fresh strategy for presenting community membership, internal structure, and inter‐cluster relation‐ships. This paper extends the basic Group‐in‐a‐Box meta‐layout, which uses a Treemap substrate of rectangular regions whose size is proportional to community size. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>